The Aftermath of Employees’ Psychological Contract Breach with The Moderation of Proactive Personality - KAYANI, MUHAMMAD BILAL; ALASAN, IMRAN IBRAHIM; IDREES, SABA; SARWAT, RABIA; ALI, MARYAM (The journal of contemporary issues in business and government, 2021)
This article aims at investigating the moderating role of proactive personality in the relationship between psychological breach of contract and workers’ outcomes which include counterproductive work behavior. Using social exchange theory, it was found that when employees face violation of their psychological contract, they may retaliate the same negative emotion in the form of counterproductive work behavior. A survey was conducted among the major cities of five provinces of Pakistan to investigate the model under investigation. The sample population were the public sector nurses of Pakistan. Structural Equation Modeling (SEM) technique was used to test and verify the hypothesis under investigation. The results didn’t support the mediating role of proactive personalities in the relationship of psychological breach of contract and counterproductive work behavior. The study attempts to fill up the gap between the psychological aspects of employees with their outcomes at the workplace.